‘BrexLit’ in Italian for Children and Adults Rosie e gli scoiattoli di St. James and La mia Londra by Simonetta Agnello Hornby - Rygielska, Małgorzata (Porównania, 2021)
The article is devoted to a comparison of two books by Simonetta Angello Hornby, placing it in the context of migration to which the author—born in 1945 in Italy and residing in Great Britain since 1972—has also touched upon in her other works. La mia Londra (My London) is an autobiographical guide to London, in which Hornby described, on the example of her own experiences, the process of adapting to life in a foreign culture. In retrospect, she spent almost half a century in this city, noting the changes in the social structure, relations with immigrants, and the lifestyle of Londoners. The main protagonist of the story Rosie e gli scoiattoli di St. James (Rosie and the Squirrels in St. James’s Park) is Rosalia Giuffrida-Watson, a nine-year-old daughter of London immigrants (Bruno from Italy and Brenda from Jamaica) who, on the day of the referendum concerning Great Britain’s future in the European Union, witness a session of animal parliament in the royal park and a clash between its residents: newcomers and autochthons. Their views, behaviour and decisions give Rosie an insight into the problems, but also the potential, connected to the processes of acculturation, cultural adaptation, and even assimilation. The cognitive context for the deliberations is provided by other “BrexLit” works.